Pendampingan Pencegahan Risiko Anak Stunting pada Masyarakat, Kader Kesehatan, dan Guru PAUD/TK - Sitti Patimah; Suchi Avnalurini Sharief; Farihah Muhsanah; Nukman Nukman; Muhammad Rachmat (Warta LPM, 2024)
The risk of stunting in Batetangnga Village is elevated because a significant number of pregnant mothers and toddlers are malnourished and lack adequate maternal knowledge. Furthermore, cadres and PAUD/TK teachers have not received any training to identify children who are at risk of stunting. The aimed of this community services are to improve participants' knowledge, awareness, motivation, and skills in stunting risk detection, prevention, and management. The results will be accurately measured, evaluated, and interpreted by skilled officers. The support method entails the following: [1] educating pregnant mothers and young mothers, health officers, and PAUD/TK teachers about (a) pregnant women who may be causing the child to stunt; (b) the risk of stunting for young children; and [2] providing health cadres and teachers of PAUD/TTK with training on identifying stunting risks in young children. The results indicated that there was a rise in knowledge from 78.9% to 81.8%, a rise in awareness from 66.7% to 73.8%, and a rise in motivation from 54.5% to 57.6% in the context of the detection, prevention, and treatment of children with stunting risks. Skilled officers promptly identify the potential for stunting. Accompanying activities are advantageous in enhancing the community's, health cadres', and PAUD/TK teachers' ability to prevent stunting in children.